Catfish Cultivation Development Strategy: A Maslahah Review (Case Study of Binjai Serdang Bedagai Village) - Ardianto, Willi; Aslami, Nuri; Harahap, Muhammad Ikhsan (Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the development strategy of catfish cultivation in Binjai Village, Serdang Bedagai Regency, from a maslahah perspective. Catfish cultivation in this village provides a significant economic contribution to the community, but still faces various challenges such as high feed prices, difficulty in obtaining quality seeds, limited capital, environmental pollution, and minimal government support. This study uses a qualitative approach with observation and interview methods, as well as a SWOT analysis to identify strengths, weaknesses, opportunities, and threats. The results show that catfish farming is included in the maslahah hajiyyah category and four main strategies can be implemented: the use of alternative feed, collaboration with catfish agents, environmentally friendly waste management, and advocacy to the village government. Maslahah hajiyyah refers to a category of public interest in Islamic law that addresses secondary needs—those that do not threaten basic survival but whose absence would create hardship and inconvenience. In Islamic economics, maslahah hajiyyah provides the basis for flexibility and facilitation in financial transactions, business practices, and economic regulations. Its function is to ease burdens, prevent undue difficulty, and support smooth socioeconomic activity while remaining within the boundaries of sharia principles.These strategies not only increase business efficiency and competitiveness but also strengthen the values of social and ecological sustainability in accordance with the principles of maslahah in Islam.